A rotational energy harvester utilizing an asymmetrically deformed piezoelectric transducer subjected only to unidirectional compressive stress - Zhonghua Zhang; Junling Chai; Yaqi Wu; Shuyun Wang; Xinyue Kan; Hongyan Tang; Junwu Kan (Energy Reports, 2023)
Energy harvesting using piezoelectric transduction offers a promising alternative to the conversion of kinetic energy like ambient vibration and rotational motion into useful electricity in self-powered electronic devices. To improve the reliability and effective bandwidth of rotational piezoelectric energy harvesters (RPEHs), a novel rotational energy harvester utilizing an asymmetrically deformed piezoelectric transducer excited by a magnetic attractive force is presented in this paper. Unlike the previous most RPEHs where piezoelectric elements experienced the symmetrical bidirectional strain, the presented piezoelectric transducer was only subjected to unidirectional compressive strain. It made the best use of the deformation characteristics of PZT vibrators where their allowable compressive stress was far greater than the allowable tensile stress, thus reducing the damage possibility of PZT vibrators under unexpected heavy loads. To prove the feasibility and explore the influence of the related structural parameters on the power generation performance, the theoretical analysis, simulation, fabrication and experiments were performed for the novel RPEH. The results showed that some parameters like the number ratio (α) and the rotary radius (R) of the exciting magnets brought a strong impact on the response characteristics of the presented RPEH. With the increasing rotary radius R, both the optimal rotating speed and effective bandwidth were decreased, whereas there were few studies on the effect of the rotary radius R of exiting force in previously reported RPEHs. In the case of rotary radius R = 60 mm, the maximum output voltage of 130 V with α = 0.5 was achieved. A maximum output power of 3.89 mW was obtained across 41 kΩ at the rotating speed of 856 r/min. It is expected this research can provide a beneficial reference for enhancing the reliability of existing RPEHs.